Prevalence and treatment of hypovitaminosis D in the haemodialysis population of Coventry. Issue 164 (November 2016) - Huish, Sharon A.; Fletcher, Simon; Dunn, Janet A.; Hewison, Martin; Bland, Rosemary
Highlights: Hypovitaminosis D is common in the haemodialysis (HD) population in Coventry. There is an absence of clear supplementation guidelines for this population. We have developed a local guideline for vitamin D supplementation in HD patients. Abstract: Low serum 25(OH)D and associated bone and non-bone related problems are not well appreciated in end stage renal disease (ESRD). Vitamin D treatment strategies in the UK currently focus almost exclusively on calcitriol [1, 25(OH)2 D], alfacalcidol or paricalcitol. In ESRD hypovitaminosis D is associated with bone loss, muscle weakness, falls, fractures and increased inflammation. National guidelines changed in 2014 and now recommend the diagnosis and treatment of low serum 25(OH)D in all patients with glomerular filtration rate (GFR) less than 30 ml/min/1.73m 2 . However as yet there are no standardized guidelines for dosage, frequency and monitoring in ESRD patients. Following a systematic review of the literature we developed a clinical guideline for cholecalciferol supplementation at University Hospitals of Coventry and Warwickshire, UK. The guideline recommends 40, 000IU cholecalciferol weekly for patients with 25(OH)D <50 nmol/L and 20, 000IU weekly for patients with 25(OH)D 50–75nmol/L; to be continued long term unless levels increase to ≥150 nmol/L. To date we have measured 25(OH)D levels in 385 in-center haemodialysis patients. Virtually all patients (95%) had serum 25(OH)D levels <75 nmol/L (65% deficient, <30 nmol/L; 30% insufficient, 30–74 nmol/L). Only 5% of patients had optimal levels (≥75 nmol/L). Our data indicates that hypovitaminosis D is prevalent in the haemodialysis population in Coventry and Warwickshire and this is likely to reflect UK haemodialysis patients, highlighting the need for a national supplementation guideline.